THE DEVELOPMENT OF A WEB-BASED INTEGRATED FINANCIAL INFORMATION SYSTEM AT PT. PURA BARUTAMA KUDUS - Andrean Richardo; Nina Setiyawati (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2021)
Pura Barutama Inc. is a printing and packaging company based in the city of Kudus, where its financial information such as pre-order reports, accounts receivable balance reports, invoice information, and income tax article 23, must be inquired manually to the finance department. So there are issues with access to the financial information that is directly linked to consumers and vendors, namely a lack of flexibility and productivity in marketing, tax, and purchasing departments. Therefore, this study aims to provide solutions to the problems by designing and building a web-based financial information system. This information system was designed using object-oriented modeling methods, namely the Unified Modeling Language (UML) method, and was built with the PHP programming language using the CodeIgniter framework and Oracle database which was directly connected to Pura Barutama Inc. This information system is expected to increase flexibility and efficiency in the marketing, taxation, and purchasing departments of the company’s financial data management process and can obtain financial details without requesting the finance department.